A sub-picosecond digitally-controlled phase delay. (1st March 2022) - Dehmeshki, D.; Frahm, E.; Rusack, R.; Saradhy, R.; Tousi, Y.
Abstract: The use of precision timing measurements will be a major tool at the HL-LHC, where it will be used to suppress pile-up and to search for long-lived particles. To control a reference clock with sub-picosecond accuracy, we have fabricated in the TSMC 65 nm process a digitally controlled phase shifter. It is composed of a chain of 66 cells, each with a digitally controlled planar wave guide with either a short or long delay. With this a reference clock's phase can be controlled to a precision of 200 fs with dynamic range of 12 ps.